2011
DOI: 10.1038/ismej.2011.154
|View full text |Cite
|
Sign up to set email alerts
|

Temperature regulation of virulence factors in the pathogen Vibrio coralliilyticus

Abstract: Sea surface temperatures (SST) are rising because of global climate change. As a result, pathogenic Vibrio species that infect humans and marine organisms during warmer summer months are of growing concern. Coral reefs, in particular, are already experiencing unprecedented degradation worldwide due in part to infectious disease outbreaks and bleaching episodes that are exacerbated by increasing SST. For example, Vibrio coralliilyticus, a globally distributed bacterium associated with multiple coral diseases, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
200
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(217 citation statements)
references
References 63 publications
3
200
1
1
Order By: Relevance
“…These in situ measurements add a new dimension to existing evidence that some coral pathogens are chemotactic towards coral mucus and other host-derived compounds (Banin et al, 2001;Koren and Rosenberg, 2006;Rosenberg et al, 2007;Meron et al, 2009;Kimes et al, 2011;Vidal-Dupiol et al, 2011;Garren et al, 2014), and that chemotaxis and motility genes can be prominent and dynamic features in the metagenomes of coral-microbial communities (Vega Thurber et al, 2009). Given the strong chemotactic responses that we observed in the laboratory experiments and ISCA deployments, we propose that motility and chemotaxis may be important phenotypes within the context of coralmicrobial interactions.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These in situ measurements add a new dimension to existing evidence that some coral pathogens are chemotactic towards coral mucus and other host-derived compounds (Banin et al, 2001;Koren and Rosenberg, 2006;Rosenberg et al, 2007;Meron et al, 2009;Kimes et al, 2011;Vidal-Dupiol et al, 2011;Garren et al, 2014), and that chemotaxis and motility genes can be prominent and dynamic features in the metagenomes of coral-microbial communities (Vega Thurber et al, 2009). Given the strong chemotactic responses that we observed in the laboratory experiments and ISCA deployments, we propose that motility and chemotaxis may be important phenotypes within the context of coralmicrobial interactions.…”
Section: Discussionsupporting
confidence: 53%
“…Some of the earliest work on marine bacterial chemotaxis demonstrated that coral and Symbiodinium exudates are potent chemoattractants (Chet and Mitchell, 1976;Bartlett and Matsumura, 1986), and chemotaxis and motility are important phenotypes for the coral pathogens Vibrio shiloi and V. coralliilyticus to locate, invade and colonise their coral hosts (Banin et al, 2001;Koren and Rosenberg, 2006;Rosenberg et al, 2007;Meron et al, 2009;Kimes et al, 2011). Recently, it has been demonstrated that V. coralliilyticus exhibits extremely strong chemotactic responses towards DMSP to locate heat-stressed colonies of its coral host, Pocillopora damicornis (Garren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Infection, microbiota and oyster health Higher mortality at 22 1C can be partially attributed to faster growth of the injected strain (Supplementary Figure 6) and/or to temperaturedependent increase in expression of virulence factors (Kimes et al, 2012). The effect of absolute temperature, however, cannot account for the difference in mortality between stressed and acclimated oysters.…”
Section: Discussionmentioning
confidence: 99%
“…The first set of experiments was conducted by growing the coral pathogen, V. coralliilyticus, at four temperatures (20°C, 23°C, 27°C and 30°C) spanning the range of seasonal mean temperatures experienced by this host-pathogen pair and include two temperatures (23°C and 27°C) that straddle the previously determined 26°C trigger point for increased virulence (Ben-Haim et al, 2003;Kimes et al, 2012). We explored the bacterium's chemotactic and chemokinetic responses at these four temperatures by using a single, homogenized pool of coral mucus collected from laboratory-cultured corals growing at a moderate temperature (25°C).…”
Section: Methodsmentioning
confidence: 99%
“…However, the effects of temperature directly on the pathogen's host-sensing behaviors are unknown. Although warmer temperatures might increase the chance of infection in several ways, such as increasing bacterial growth rates or virulence (Kimes et al, 2012), the effect of temperature on pathogen motility appears particularly important because all putative bacterial pathogens of corals that have been identified thus far are motile (Garren et al, 2014), with both motility and increased seawater temperatures independently implicated in the infection process (Banin et al, 2001;Meron et al, 2009).…”
Section: Introductionmentioning
confidence: 99%